Aligning recycling behaviors and the recycling system – Towards a full cycle of materials and behavioral methods. (1st February 2022) - Pegels, Anna; Castañeda, Jorge Luis; Humphreys, Carolina; Kötter, Caroline; Negre, Mario; Weidner, Christian; Kutzner, Florian
Highlights: Full-cycle behavioral approach from context-analysis to up-scaling. Cost-effective interventions: message variations in letters and calendars. Strong experimental effects. Effects were sustained after six months. Results based on observed behavior rather than self-reports. Abstract: In a transdisciplinary project with the Municipality of Trelew (Argentina), we assessed barriers to households disposing of separated waste, developed supportive behavioral interventions, tested the interventions in a randomized controlled trial, and supported the Municipality in upscaling the most successful and cost-effective intervention to a total of 20, 000 households. The interventions were designed to address the three main barriers to waste separation detected through a baseline study: a lack of knowledge on how separation works; the additional hassle it represents; and the self-regulation challenge it poses. The interventions consisted of envelopes containing simplifying information, empathetic messages, a magnetic calendar acting as a reminder, or a combination thereof. The interventions roughly halved the prevalence of bags containing unusable mixed waste two weeks after the intervention. This impact was still present after six months. We did not find evidence for an additional effect of empathetic messages or the reminder. Based on these results, the simplified information intervention was rolled out. The results provide evidence of the high potential of using the full range of behavioral methods to increase sustainable behaviors, particularly in the context of limited options to adapt the waste management system as such.